Differences in psychosocial impact of lockdown and life satisfaction among Nigerian working adults during Covid-19 - Sunday Itasanmi; Violet Ekpenyong; Solomon Ojedeji (SIMULACRA: JURNAL SOSIOLOGI, 2020)
This study assessed differences in the psychosocial impact of lockdown and life satisfaction among Nigerian working adults during the Covid-19 pandemic. The study was hinged on the social stress theory. Five hundred and eighteen (518) Nigerian working adults participated in the study using a convenience sampling technique. Two sets of questionnaires were the main instruments of data collection and were complemented by in-depth interview. Quantitative data collected were analyzed using one-way ANOVA, while the qualitative data was thematically analyzed. Findings revealed, amongst others, that livelihood activities of working adults in Nigeria were significantly affected by the Covid-19 lockdown. Working adults who lost jobs during Covid-19 lockdown reported a higher psychosocial impact of the lockdown compared to those who stopped working, worked at home and those who worked at the office during the Covid- 19 lockdown in the country. Based on the findings, it was recommended among others, that there is a need for concerted efforts by stakeholders in the country to provide enabling environment for working adults to recover and sustainably return to reasonable livelihood from the shocks occasioned by Covid-19 pandemic.